PELATIHAN BANTUAN HIDUP DASAR DAN PENANGANAN TERSEDAK TEHADAP PENINGKATAN PENGETAHUAN DAN KETERAPILAN SISWA SMA - akbar nur (Caring : Jurnal Keperawatan, 2021)
Background: An Emergency is an event that occurs suddenly to cause a person to need treatment and help quickly and accurately. One of the actions that can be done by ordinary people and medical personnel in handling emergency cases is to provide Basic Life Support (BLS) which is an effort to prevent the occurrence of cardiac arrest and respiratory arrest. Objective: This research was conducted to determine the effect of Basic Life Support (BLS) and the handling of choking on improving the knowledge and skills of students of Senior High School3 Mamuju Method: This study used a One-group pre-test-post test design to find out knowledge and skills in handling Basic Life Assistance (BLS) and choking treatment in Mamuju 3 High School students. The subjects used in this study were students of Senior High School 3 Mamuju with a total of 35 respondents. Analysis of research data using SPSS and hypothesis testing using the Paired t-test. Results: Statistical test results with Paired t-test had a significant influence before and after Basic Life Assistance (BLS) training and choking treatment with a significance value p-value = 0.001 knowledge, Basic Life Support skills P-Value = 0.002 and choking handling skills P-Value = 0.001 with a significance level of 0.05 (P <0.05). Conclusion: Basic Life Assistance Training (BHD) and effective choking management to improve the knowledge, BHD skills and choking handling skills of SMuju 3 Mamuju students so that it is expected that handling emergency cases that can be found in the field can be dealt with quickly and appropriately.